ANALISIS TERHADAP JAWABAN PESERTA DIDIK KELAS VIII SMP DALAM MENYELESAIKAN SOAL SPLDV DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Ratnasari, Rika; Nurjanah; Heru Sujiarto; Usep Kosasih (Uninus Journal of Mathematics Education and Science (UJMES), 2024)
In the process of learning mathematics there is a very important and inseparable process of solving problems. Mathematical problems are still always found difficult by students in the process of solving them, so not many students can do problem solving even though students are required to be able to solve math problems until they find the right answer for the problem. The purpose of this study was to describe the answers of class VIII SMP students in solving SPLDV questions in terms of mathematical problem solving abilities. This study used descriptive qualitative method. The subjects in this study consisted of three students, each of whom had problem solving abilities based on high, medium and low categories. The results of this study were that students in class VIII B at SMP Pasundan 1 Banjaran in the high category could complete the problem solving stages according to Polya and were able to explain the process of solving SPLDV questions. For students in the medium category, they are able to explain the process of solving SPLDV questions, but they are still not quite right in completing the problem solving stages according to Polya. Meanwhile, students in the low category could not complete the problem solving steps according to Polya in solving SPLDV questions.